Laughing fit to kill : black humor in the fictions of slavery - Carpio, Glenda (Oxford University Press, 2008)
Introduction. 1. "Laffin fit ter kill:" Black Humor in the Fiction of William Wells Brown and Charles W. Chesnutt. 2. The Conjurer Recoils: Slavery in Richard Pryor and Chappelle's Show. 3. Conjuring the Mysteries of Slavery: Voodoo, Fetishism, and Stereotype in Ishmael Reed's Flight to Canada. 4. "A Comedy of the Grotesque": Robert Colescott, Kara Walker and the Iconography of Slavery. 5. The Tragicomedy of Slavery in Suzan-Lori Parks' Early Plays. Notes. Bibliography. Index